Caste flexibility and variation according to the colony cycle in the swarm-founding wasp, Parachartergus fraternus (Gribodo) (Hymenoptera : Vespidae : Epiponini) - Mateus, S.; Noll, F. B.; Zucchi, R. (Kansas Entomological Soc, 2004)
Differences between castes and related aspects in Parachartegus fraternus (Gribodo) have been studied in various stages of the colony cycle. Five colonies from three colony development stages (namely, pre-emergence, worker-producing and male-producing) were analyzed. The main results were: irrespective of colony age, castes were always morphologically indistinguishable; non-inseminated ovary-developed females were found in four colonies; because differences of castes were physiological rather than morphological, castes are evidently post-imaginally determined and this is probably taking place according to the colony conditions. These findings support the occurrence of caste totipotency in Parachartergus fraternus.
Keywords: Polistinae; Epiponini; Parachartegus fraternus; caste differences; colony cycle; productivity